FUNDING AND FINANCE ISSUES RELATED TO THE DECOMMISSIONING OF BRAZILIAN NPPS - Daniel Artur Pinheiro Palma; Anna Leticia Barbosa de Souza; Amir Zacarias Mesquita (Brazilian Journal of Radiation Sciences)
It has been a consensus in the Academy that, for a nation to grow and develop in economic terms, an adequate supply of power should be available to provide its industrial sector as well as the needs of its people. Brazil did in the past make the decision to use the power generated from a nuclear source in its power generation matrix. The country today has two nuclear power plants in operation, Angra I and Angra II, with a third plant currently under construction, Angra III. The Angra I facility is nearly 40 years old and, should this country not manage to extend its lease of life, it should be decommissioned and taken apart, as provisioned for in prevailing legislation. In order to face the decommissioning costs of a nuclear power generation facility a sizeable amount of financial resources should be available to implement the decommissioning plan the operator is required to submit to the regulatory body. As the expected operating life of a nuclear power plant is of 40 years, some extensions were added to it to see the facilities go through successive and different governments and economic plans. This work studies some of the economic and financial aspects that go into the decommissioning of the Angra I power plant, pursuant to the IAEA documents published on the subject, covering different scenarios for yearly interest and the manner of the deposits, such as those of an uniform series of deposits and those of a growing and finite arithmetic progression.